2011
DOI: 10.1111/j.1349-7006.2011.02053.x
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 4D, a lymphocyte semaphorin, enhances tumor cell motility through binding its receptor, plexinB1, in pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant tumor, for which the development of new biomarkers and therapeutic targets has become critical. The main cause of poor prognosis in PDAC patients is the high invasive and metastatic potential of the cancer. In the present study, we report a new signaling pathway that was found to mediate the enhanced tumor cell motility in pancreatic cancer. Semaphorin 4D (Sema4D) is a ligand known to be expressed on different cell types, and has been reported to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 25 publications
2
41
0
2
Order By: Relevance
“…Cancer cell proliferation and tumour-related angiogenesis may vary to a greater extent under the influence of these molecules. Increased Sema4D and plexin-B1 expression in pancreatic ductal adenocarcinoma patients is correlated with lymph node involvement and metastasis (21). Similarly, in soft tissue sarcoma patients the elevated expression of Sema4D is associated with an increased mitotic division of cancer cells.…”
Section: Introductionmentioning
confidence: 82%
“…Cancer cell proliferation and tumour-related angiogenesis may vary to a greater extent under the influence of these molecules. Increased Sema4D and plexin-B1 expression in pancreatic ductal adenocarcinoma patients is correlated with lymph node involvement and metastasis (21). Similarly, in soft tissue sarcoma patients the elevated expression of Sema4D is associated with an increased mitotic division of cancer cells.…”
Section: Introductionmentioning
confidence: 82%
“…Plexins also participate in regulating angiogenesis. Plexins A1-A4 have been described as transducers of antiangiogenic signals conveyed by class-3 semaphorins such as sema3F, while the SEMA4D-PlexinB1 has been known as a potent inducer of angiogenesis and is associated with poor prognosis in various solid tumors (15,16). Angiogenesis and lymphangiogenesis intersect in the regulation of tumor microenvironment, and several recent studies also suggested that semaphorins may affect lymphangiogenesis (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical (IHC) analysis of several tumor types revealed that both SEMA4D and its receptors are overexpressed on various human and murine tumors, including human head and neck, prostate, colon, breast, and lung cancers (20). Moreover, elevated expression correlates with invasive disease and poor prognosis in human cancer (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%